An 18-Month-Old Child with Infantile Pompe Disease: Oral Signs - Derya Ceyhan; Burcu Gucyetmez Topal (Case Reports in Dentistry)
We aim to create an information platform by contributing orodental findings of Pompe disease to literature. An 18-month-old male patient with Pompe disease was referred to our clinic due to swelling of the gums. In first dental examination, a nonfluctuant, normal gingiva colored swelling at the right anterior region of maxilla was detected. His parents were recommended to perform finger massage to the region. Six months later, 51, 52, 62, and 74 numbered teeth had erupted, there was a fusion between 51 and 52 numbered teeth, 84 numbered tooth was seen to be erupted, and a swelling at the site of this tooth, similar to previous one, was present. Finger massage was recommended for this area as well, and the swelling was found to have decreased at the follow-up, one week later. Tooth eruption problems and developmental dental abnormalities should be included in the signs for Pompe disease.